Financial Literacy Self Control and PayLater Financial Management: Literasi Keuangan, Pengendalian Diri, dan Pengelolaan Keuangan PayLater - Ayu Stya Ningrum; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background The rapid growth of Buy Now Pay Later services has reshaped financial behavior among young consumers. Specific Background Shopee PayLater is widely used by Generation Z, raising concerns regarding financial management behavior. Knowledge Gap Empirical studies examining financial literacy, self control, and financial attitudes in the context of PayLater usage remain limited, particularly at the regional level. Aims This study aims to analyze the relationships between financial literacy, self control, and financial attitudes toward financial management behavior among Shopee PayLater users. Results The findings indicate that financial literacy, self control, and financial attitudes are associated with users’ financial management behavior. Novelty This study integrates behavioral and financial variables within the specific context of Shopee PayLater usage among Generation Z. Implications The results provide insights for improving financial awareness and responsible PayLater usage among young consumers. Keywords: Financial Literacy, Self Control, Financial Attitude, Financial Management Behavior, Shopee PayLater Key Findings Highlights: Financial knowledge relates to responsible management of PayLater usage Behavioral control aligns with users’ financial management patterns Financial attitudes correspond with PayLater financial practices